Upper limb muscle strength and endurance as predictors of successful extubation in mechanically ventilated patients : a predictive correlational study - Van Rooijen, Agatha Johanna (University of Pretoria, 2021)
Thesis (PhD (Physiotherapy)) University of Pretoria, 2020.